2006
DOI: 10.1017/asc200696
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between temperament and breeding traits in Limousin heifers

Abstract: The aim of this study was to assess the potential consequences of selection for less aggressive or active animals during handling by estimating genetic correlations between different criteria of temperament and Limousin heifer breeding traits. Data consisted of the records collected from 1992 to 2004 at the progeny test station of Limousin AI sires. Six traits recorded during the same behavioural test – the so-called docility test – were considered to describe the heifer's temperament: aggressiveness against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 17 publications
4
57
1
7
Order By: Relevance
“…In cattle, the majority of research on temperament explored the responses to a novel testing arena, a novel object or to the human presence or handling (Phocas et al, 2006). According to Burrow (1997), the definition of temperament in cattle breeding and genetics has been restricted to the behavioral response of the animal handling by humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle, the majority of research on temperament explored the responses to a novel testing arena, a novel object or to the human presence or handling (Phocas et al, 2006). According to Burrow (1997), the definition of temperament in cattle breeding and genetics has been restricted to the behavioral response of the animal handling by humans.…”
Section: Introductionmentioning
confidence: 99%
“…This score refers to the time taken (s) for an animal to cover 1.7 m after leaving a weighting crush. The aggressiveness score (AG) used by Phocas et al (2006) indicates whether the animal threatened the handler in order to measure temperament in heifers. They also defined a docility score (DO) combining several ways of measuring the -E-mail: saquei@fcav.unesp.br behavioral response of the animal to the handler in a linear equation to analyze temperament.…”
Section: Introductionmentioning
confidence: 99%
“…In hens, Xu et al (2010) found three QTL involved in egg incubation behaviour, which was put at a disadvantage by selective breeding; among these QTL one was linked to the DRD1 gene, which encodes a dopamine receptor. Phocas et al (2006) found, in beef cattle, that the more maternal cows showed a slightly higher milking ability, but Hoppe et al (2008) found no association of maternal reaction to progeny removal with progeny growth. Higher maternal ability is genetically correlated with lower progeny mortality in pigs (Grandinson et al, 2003;Hellbrü gge et al, 2008), whereas Hoppe et al (2008) found no genetic association in cattle.…”
Section: Maternal Behaviourmentioning
confidence: 95%
“…Dé sauté s et al (2002) found different QTL in pigs to be associated with locomotion on SSC1, or with exploration on SSC8. In beef cattle, locomotion in open field shows moderate heritability and is correlated unfavourably with growth and milk production (Phocas et al, 2006). In dairy cattle, QTL associated with vocalization and locomotion when isolated from the herd are located mainly on BTA16 and BTA19 (Gutierrez-Gil et al, 2008).…”
Section: Genetics Of the Behavioural Response To Changes In The Physimentioning
confidence: 99%
See 1 more Smart Citation